Influence of Service Prices and Rupiah Exchange Rates on FOB Export Volume in PT Samudera Perdana Selaras (2017-2022) - Ady Pamungkas, Rico Arizki; Salsiyah, Sri Marhaeni; Zaenuddin, Achmad - (Admisi dan Bisnis, 2024)
PT Samudera Perdana Selaras was founded by Rory Riyanto as a Limited Liability Company in 2004, operating in the field of transportation and shipping services (Integrated Global Logistic). Research was conducted to analyze the effects of service prices and the exchange rate of the Indonesian Rupiah, both individually and simultaneously, on the volume of exports free on board. Data was collected through observation mechanisms carried out at PT Samudera Perdana Selaras, as well as secondary data taken from the Central Statistics Agency (Badan Pusat Statistika). The results of the research analysis show that the hypothesis testing, either simultaneously using 40ft and 20ft containers, indicates that all independent variables, namely service prices and the exchange rate of the Rupiah, significantly influence the volume of exports free on board at PT Samudera Perdana Selaras. Meanwhile, in the partial t-test, there is significance between each independent variable and the dependent variable. The service price variable has a negative and significant influence, whereas the exchange rate of the Rupiah variable has a positive and significant influence on the volume of exports free on board, both in the 20ft and 40ft containers. Given the significant contribution of service prices to the volume of exports free on board, PT Samudera Perdana Selaras needs to pay attention to setting the offered service prices to customers (Exporters), thus potentially increasing the volume of exports free on board over time